Pengaruh Permintaan, Produk Domestik Bruto (Pdb) Dan Kurs Dollar Amerika Serikat Terhadap Impor Semen Di Indonesia Tahun 1993-2012 - Praharsinidewi, Desak Ayu Ketut; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 5, Mei 2015 (pp. 348 - 607), 2015)
Cement is one of the commodities imported Indonesia to support the construction sector in the Indonesian economy. Efforts to control the price and import of cement is done in anticipation of shortages of cement in Indonesia. The purpose of this study was to determine the effect of demand, Gross Domestic Product, and the US dollar exchange rate on imported cement in Indonesia in 1993 - 2012. The data analysis using multiple linear regression. The results showed demand, gross domestic product and the US dollar exchange rate simultaneously significant effect on the import of cement in Indonesia in 1993-2012. Demand, gross domestic product is partially positive and significant impact on the import of cement in Indonesia in 1993-2012. While the US dollar exchange rate partially negative and significant effect on the import of cement in Indonesia in 1993-2012.
Keywords: impor semen; permintaan; produk domestik bruto; kurs dollar Amerika Serikat